Allergic diseases and Meniere's disease: a bidirectional Mendelian randomization - Hongru Qin; Meng Huang; Weiming Liang; Guojing Wu; Mengjia Tan; Junli Zhang; Wenyong Chen (Brazilian Journal of Otorhinolaryngology)
Objectives: Allergic diseases and Meniere's disease found to have a possible link in observational study. However, the potential causal relationship between the two is unclear. Therefore, we aimed to explore the causal relationship between allergic diseases and Meniere's disease using a new data analysis technique called bidirectional Mendelian randomization study. Method: Summary-level statistics for Meniere's disease and three allergic diseases (asthma, allergic rhinitis, eczema/dermatitis) were obtained from large-scale genome-wide association studies. The inverse variance weighted method was used as the primary measure, supplemented by MR-Egger regression and the weighted median method. To ensure the reliability of the conclusions, Cochran's Q, MR-Egger intercept, MR-PRESSO test, leave-one-out test, and MR Steiger test were used. Results: Inverse-variance weighted method showed asthma (p = 0.008, OR = 3.908, 95% CI 1.424–10.724, adjust_p = 0.024), allergic rhinitis (p = 0.026, OR = 24.714, 95% CI 1.479–412.827, adjust_p = 0.026) and eczema/dermatitis (p = 0.019, OR = 3725.954, 95% CI 3.795 to 3,658,399.580, adjust_p = 0.029) all had a significant effect on Meniere's disease. Reverse Mendelian randomization studies have shown that Meniere's disease does not increase the risk of three allergic diseases. Sensitivity analysis showed no horizontal pleiotropy and heterogeneity for each trait. Conclusion: Our Mendelian randomization analysis supports a positive causal relationship between three allergic diseases (asthma, allergic rhinitis, eczema/dermatitis) and Meniere's disease. This suggests that physicians should pay more attention to the Meniere's patient's allergy history and consider allergy avoidance as part of their treatment plan. Level of evidence: Mendelian Randomized (MR) studies are second only to randomized controlled trials in terms of the level of evidence.